Assessment of potentially inappropriate medications using the EU (7)-PIM list and the Swedish quality indicators - Wamil, Natacha (Int J Clin Pharm, 2019)
Background Several tools to evaluate the appropriateness of prescriptions have been developed over the years. Objective To compare the prevalence of potentially inappropriate medication (PIM) among elderly, using the European Union (EU) (7)-PIM list and the Swedish quality indicators. Secondary objectives were to investigate factors associated with the use of PIMs using the two tools. Setting Medical ward in a hospital in Northern Sweden. Methods Medical records for patients aged ≥ 65 years admitted to the medical ward were reviewed by clinical pharmacists from September to November 2015 and from February to April 2016. PIMs were identified through the abovementioned identification tools. Main outcome measure Prevalence of PIMs. Results Of 93 patients, 18.3% had one PIM according to the Swedish quality indicators. The most common PIM class was non-steroidal anti-inflammatory drugs and diclofenac was one of the most commonly prescribed PIMs. According to the EU (7)-PIM list, 45.2% of the study population was prescribed one or more PIMs. The most common PIM class was hypnotic and sedative drugs, and the most frequently prescribed PIM was apixaban. No significant associations between PIMs and different factors were found using either identification tool. Conclusion The prevalence of PIMs was relatively low in the study sample according to the Swedish guidelines but high according to the EU (7)-PIM list. Different evaluation tools might give inconclusive results, but it is still important to continuously evaluate the need for PIMs in older patients in order to improve drug treatment and to decrease the risk of adverse drug reactions.